From two-dimensional graphene oxide to three-dimensional honeycomb-like Ni3S2@graphene oxide composite: insight into structure and electrocatalytic properties. Issue 12 (20th December 2017) - Wei, Xinting; Li, Yueqiang; Xu, Wenli; Zhang, Kaixuan; Yin, Jie; Shi, Shaozhen; Wei, Jiazhen; Di, Fangfang; Guo, Junxue; Wang, Can; Chu, Chaofan; Sui, Ning; et al.
Abstract : Three-dimensional (3D) graphene composites have drawn increasing attention in energy storage/conversion applications due to their unique structures and properties. Herein, we synthesized 3D honeycomb-like Ni3 S2 @graphene oxide composite (3D honeycomb-like Ni3 S2 @GO) by a one-pot hydrothermal method. We found that positive charges of Ni 2+ and negative charges of NO3 − in Ni(NO3 )2 induced a transformation of graphene oxide with smooth surface into graphene oxide with wrinkled surface (w-GO). The w-GO in the mixing solution of Ni(NO3 )2 /thioacetamide/H2 O evolved into 3D honeycomb-like Ni3 S2 @GO in solvothermal process. The GO effectively inhibited the aggregation of Ni3 S2 nanoparticles. Photoelectrochemical cells based on 3D Ni3 S2 @GO synthesized at 60 mM l −1 Ni(NO3 )2 exhibited the best energy conversion efficiency. 3D Ni3 S2 @GO had smaller charge transfer resistance and larger exchange current density than pure Ni3 S2 for iodine reduction reaction. The cyclic stability of 3D honeycomb-like Ni3 S2 @GO was good in the iodine electrolyte. Results are of great interest for fundamental research and practical applications of 3D GO and its composites in solar water-splitting, artificial photoelectrochemical cells, electrocatalysts and Li-S or Na-S batteries.